PENGARUH PERSONAL SELLING DAN SALES PROMOTION TERHADAP KEPUTUSAN PEMBELIAN LAPTOP PADA KONSUMEN - Kosim, Steffy Andreani (Universitas 17 Agustus 1945 Surabaya, 2019)
This research aims at determining (1) the influence of personal selling partially to purchase decision (2) the influence of sales promotion partially to purchase decision and (3) the influence of personal selling and sales promotion simultaneously to the decision of purchasing laptops on consumers of Pegasus Computer Tebing Tinggi. Personal selling and sales promotion are promotional tools that are part of the marketing mix that can support purchase decisions. This research was conducted by distributing questionnaires to 100 respondents who are consumers of Pegasus Computer Shop Tebing Tinggi. The method used for this research is quantitative method with correlation analysis techniques and multiple linear regression whereas for hypothesis testing is used coefficient of determination test (R2), t test and F test. The result shows that there is a partial and simultaneous influence between personal selling and sales promotion to purchase decision.Â Keywords:Â Personal selling, sales promotion, purchase decision